2022
DOI: 10.3390/diagnostics12030644
|View full text |Cite
|
Sign up to set email alerts
|

Can Self-Administered Rapid Antigen Tests (RATs) Help Rural India? An Evaluation of the CoviSelf Kit as a Response to the 2019–2022 COVID-19 Pandemic

Abstract: This paper evaluates India’s first officially approved self-administered rapid antigen test kit against COVID-19, a device called CoviSelf. The context is rural India. Rapid antigen tests (RATs) are currently popular in situations where vaccination rates are low, where sections of the community remain unvaccinated, where the COVID-19 pandemic continues to grow and where easy or timely access to RTPCR (reverse transcription-polymerase chain reaction) testing is not an option. Given that rural residents make up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It also showed that the POC RT-PCT displayed the characteristics of a POC test, with a short turnaround time for quick patient isolation. The implementation of the first official approved self-administered rapid antigen tests (RATs), CoviSelf, was assessed as part of a community-level COVID-19 pandemic response in rural India [ 3 ]. Results of the study show that self-administered RATs have potential in rural settings as they are cheap, quick and reasonably reliable.…”
mentioning
confidence: 99%
“…It also showed that the POC RT-PCT displayed the characteristics of a POC test, with a short turnaround time for quick patient isolation. The implementation of the first official approved self-administered rapid antigen tests (RATs), CoviSelf, was assessed as part of a community-level COVID-19 pandemic response in rural India [ 3 ]. Results of the study show that self-administered RATs have potential in rural settings as they are cheap, quick and reasonably reliable.…”
mentioning
confidence: 99%